2019
DOI: 10.1021/acsomega.9b00917
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bioavailability of Curcumin in Gliadin-Protected Gold Quantum Cluster for Targeted Delivery

Abstract: This study deals with the synthesis of a gliadin-stabilized gold quantum cluster (AuQC) for the encapsulation of curcumin (CUR) and its targeted delivery to the cancer cell. CUR is an anticancer drug containing a hydrophobic polyphenol derived from the rhizome of Curcuma longa . The utilization of CUR in cancer treatment is limited because of suboptimal pharmacokinetics and poor bioavailability at the tumor site. In order to improve the bioavailability of CUR, we have encapsulated it int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The key technical challenge here is to develop an appropriate method to construct the protein superstructures, so that their biological activities can be retained. There have been crosslinked protein nanoparticles derived from gelatin [ 41 ], albumin [ 42 ], and gliadin [ 43 ]. The existing fabrication methods such as coacervation and desolvation usually unfold the proteins to decrease the intramolecular hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The key technical challenge here is to develop an appropriate method to construct the protein superstructures, so that their biological activities can be retained. There have been crosslinked protein nanoparticles derived from gelatin [ 41 ], albumin [ 42 ], and gliadin [ 43 ]. The existing fabrication methods such as coacervation and desolvation usually unfold the proteins to decrease the intramolecular hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…From the DSC thermogram, it was found that curcumin (fig. 4A) exhibits a sharp endothermic peak at 185.22 °C, indicating its melting point, respectively [60]. The thermogram of the ethylcellulose (fig.…”
Section: Fig 3: Ft-ir Spectrums Of (A) Curcumin (B) Ethylcellulose (C) Stearic Acid (D) Physical Mixture (E) Blank Lphnps (Bn-1) (F) Curcmentioning
confidence: 94%
“…For example, the Cur and lipoic acid (LA) loaded gold–iron oxide nanocomposite developed by Ghorbani et al [ 102 ] has been functionalized with GSH to increase cellular uptake of the system in GSH receptor-positive astrocyte cells, thus ameliorating its ability to bypass the blood–brain barrier. Mahalunkar et al [ 105 ] and Mathew et al [ 103 ] employed folic acid (FA) in Cur-loaded systems projected to target cancer cells that overexpress membrane-associated FA receptors in comparison with normal tissues. Conjugation with the MUC-1 (mucin-1) aptamer has allowed the Cur-loaded system described by Alibolandi et al [ 101 ] to target colorectal adenocarcinoma cells since MUC-1 is overexpressed on several tumor cells and can modulate their invasive and metastatic potential.…”
Section: Gold-based Hybrid Nanosystemsmentioning
confidence: 99%
“…FA, which has two free -COOH groups and is a tumor-targeting ligand, is particularly suited for this type of functionalization [ 142 ]. Mathew et al combined the targeting properties of FA and the excellent optical and delivery properties of Au quantum clusters (AuQCs) in a Cur-containing multifunctional hybrid system for anticancer therapy and bioimaging [ 103 ]. First, Au clusters of an average size of ~2 nm were coated with gliadin, a class of Pro- and Gln-rich proteins present in the wheat gluten with a high capability of binding hydrophobic molecules also due to the high content of nonpolar amino acids in its primary structure [ 143 ].…”
Section: Gold-based Hybrid Nanosystemsmentioning
confidence: 99%
See 1 more Smart Citation